Tanggung Jawab Manajemen Hotel Hilton Bandung Dalam Membangun Lingkungan Kerja yang Positif bagi Karyawan - Wanda Alis Antika; Sesilia Santril Saputri (Asosiasi Peneliti Dan Pengajar Ilmu Sosial Indonesia, 2025)
Hotel Management's Responsibility towards employees plays an important role in creating a positive work environment. Management is responsible for providing training and development to improve employee skills and abilities, as well as ensuring employee welfare through fair policies. This research aims to identify Management Responsibilities especially at Hilton Bandung Hotel in building an atmosphere that supports employee comfort and well-being. The method used from this research is qualitative method with interviews to HRD and Employees. The result of this study shows that the Management of Hilton Bandung Hotel implements various strategies, such as training, welfare policies, and open communication to improve employee motivation and work. The implication of this research is that a positive work environment can improve employee performance, as well as contribute to the quality of service provided to guests, thus impacting the reputation and sustainability of the hotel. This research is expected to be a reference for other hotel management in creating a better work environment.